Analisis Pengaruh Tingkat Pendidikan Ibu dan Pemberian ASI Eksklusif terhadap Kejadian Stunting pada Balita di Provinsi Kalimantan Tengah - Rezqi Handayani; Nurul Qamariah; Haris Munandar (Jurnal Surya Medika (JSM), 2022)
Based on data from the 2019 Indonesian Toddler Nutritional Status Study (SSGBI) the lowest prevalence of stunting was Murung Raya (17.45%), Lamandau (17.83%), and West Kotawaringin (23.98%). Meanwhile, the districts with the highest prevalence were Kapuas (42.37%), East Kotawaringin (39.87%), and East Barito (38.53%). The results of routine monitoring of nutritional status carried out by districts/cities through E-PPBGM stated that the percentage of undernourished children aged 0-59 months in Central Kalimantan Province in 2019 was 10.1 %. One of the bad effects of nutritional problems is stunting. The case of stunting in children under five is still a health problem that needs to be watched out for in Indonesia. One of the factors causing stunting is the mother's education level and the provision of breast milk (ASI) to infants and toddlers. The study analyzed the relationship between maternal education level and exclusive breastfeeding for children under five with stunting in Central Kalimantan Province. This study used a cross-sectional research design with univariate data analysis and bivariate analysis. The Univariate analysis aims to describe the distribution of children under five by age, by gender, level of mother's education, distribution of exclusive breastfeeding, and nutritional status of children under five based on health profile data in the form of a frequency distribution table. Bivariate analysis in this study used the Chi-square test. The results showed that there was a significant or significant relationship between the level of mother's education and exclusive breastfeeding with the incidence of stunting in children under five in the province of Central Kalimantan in 2019.